TAAT II Supervision Mission Workshop - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2023)
Technologies for African Agricultural Transformation II Supervision Mission Workshop at IITA HQ from 29 May - 3 June 2023. Photo by IITA.